2023
DOI: 10.1259/dmfr.20220081
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence system for automated landmark localization and analysis of cephalometry

Abstract: Objectives: Cephalometric analysis is essential for diagnosis, treatment planning and outcome assessment of orthodontics and orthognathic surgery. Utilizing artificial intelligence (AI) to achieve automated landmark localization has proved feasible and convenient. However, current systems remain insufficient for clinical application, as patients exhibit various malocclusions in cephalograms produced by different manufacturers while limited cephalograms were applied to train AI in these systems. Methods: A robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Table 1 presents the summarised studies on the application of AI in cephalometric analysis. In total, 23 articles were included based on both AI algorithms designed by their authors for the purpose of a specific study [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] and web-based software available on search engines and mobile applications [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The studies focused on comparing the reliability of AI algorithms in localising cephalometric landmarks on lateral cephalometric radiographs with the manual tracing of these points; differences between various algorithms were also examined [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents the summarised studies on the application of AI in cephalometric analysis. In total, 23 articles were included based on both AI algorithms designed by their authors for the purpose of a specific study [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] and web-based software available on search engines and mobile applications [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The studies focused on comparing the reliability of AI algorithms in localising cephalometric landmarks on lateral cephalometric radiographs with the manual tracing of these points; differences between various algorithms were also examined [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Jiang et al developed a novel and accurate system for automatic cephalometric landmark location and analysis based on a two-stage cascade CephNet system [ 33 ]. The system consisted of two-stage neural networks, from which the first aimed to detect 10 regions of interest (ROI), each containing 1–9 landmarks, and in the second stage, the landmarks were accurately located in the ROIs.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies on ANN in orthodontics have reported their results on automated cephalometric landmark identification 12,18–25 . Furthermore, commercial orthodontic products for orthodontic diagnosis and treatment evaluation are already in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on ANN in orthodontics have reported their results on automated cephalometric landmark identification. 12,[18][19][20][21][22][23][24][25] Furthermore, commercial orthodontic products for orthodontic diagnosis and treatment evaluation are already in clinical use. Clinicians can choose these AI products and benefit from orthodontic treatment and clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“… Author/year Country Architecture Objective Sample size SDR (successful detection rate) Alshamrani et al (2022) ( Alshamrani et al, 2022 ) Saudi Arabia CNN (autoencoder-based Inception layers) Generate a Bjork–Jarabak and Ricketts cephalometrics automatically. 100 Basic autoencoder model trained on Set 1 2.0 mm: 64% 2.5 mm: 69% 3.0 mm: 72% 4.0 mm: 77% 150 Model autoencoder wider Paddup box set 2 2.0 mm: 71% 2.5 mm: 75% 3.0 mm: 78% 4.0 mm: 84% El-Fegh et al (2008) ( El-Fegh et al, 2008 ) Libya/ Canada CNN A new approach to cephalometric X-ray landmark localization > 80 2.0 mm: 91% El-Feghi et al (2003) ( El-Feghi et al, 2003 ) Canada MLP A novel algorithm based on the use of the Multi-layer Perceptron (MLP) to locate landmarks on a digitized X-ray of the skull 134 2.0 mm: 91.6% Hwang et al (2021) ( Hwang et al, 2021 ) South Korea CNN (YOLO version 3) To compare an automated cephalometric analysis based on the latest deep learning method 200 2.0 mm: 75.45% 2.5 mm: 83.66% 3.0 mm: 88.92% 4.0 mm: 94.24% Jiang et al (2023) ( Jiang et al, 2023 ) China CNN (A cascade framework “CephNet”) Utilizing artificial intelligence (AI) to achieve automated landmark localization in patients with various malocclusions 259 1.0 mm: 66.15% 2.0 mm: 91.73% 3.0 mm: 97.99% Kafieh et al (2009) ( Kafieh et al, 2009 ) Iran ASM As a new method for automatic landmark detection in cephalometry, they propose two different methods for bony structure discrimination in cephalograms. 63 1.0 mm: 24.00% 2.0 mm: 61.00% ...…”
Section: Methodsmentioning
confidence: 99%